Detrital zircon ages from a Lower Ordovician quartzite of the A°stanbul exotic terrane (NW Turkey): evidence for Amazonian affinity - Ustaomer, Petek Ayda; Ustaomer, Timur; Gerdes, Axel; Zulauf, Gernold (SPRINGER, 2011)
NW Turkey is a mosaic of several continental and oceanic units, that were amalgamated by collisional and strike-slip tectonics. One of the continental units is the A degrees stanbul terrane, the Palaeozoic strata of which comprise an Early Ordovician to Early Carboniferous transgressive sedimentary sequence. The basement to the Palaeozoic succession is exposed in the Bolu Massif and is represented by a thick meta-volcanic unit intruded by Late Neoproterozoic (ca. 575 Ma) felsic magma. This meta-igneous basement is considered to be a sliver of the Cadomian magmatic arc. Unconformably overlying Early Ordovician strata start with red fluvial clastics (ca. 3,000 m), overlain by shallow marine quartzites ( 90% concordant) range from 530 to 2550 Ma. The dominance (44 grains) of Neoproterozoic zircon ages (around 540, 570, 600-640 and 700-800 Ma) rules out any link of the A degrees stanbul terrane with Baltica. The large amount (40 grains) of Grenvillian and Meso- to Palaeo-proterozoic ages (around 1.0-1.2, 1.3-1.6, 1.7-1.8, and 1.9-2.1 Ga) in the zircon population further rules out a link to Cadomian and Minoan terranes, but is indicative for Amazonian source areas. The new age data suggest the A degrees stanbul terrane to be a peri-Gondwanan terrane that was located at the northwestern margin of Gondwana close to Amazonia. This terrane should have travelled a large distance in the Phanerozoic times.
Keywords: Istanbul terrane; Detrital zircon ages; Early Ordovician; Amazonia; TEPLA-BARRANDIAN UNIT; EARLY PALEOZOIC EVOLUTION; PERI-GONDWANAN TERRANES; CADOMIAN ACTIVE MARGIN; PLATE TECTONIC MODEL; OSSA-MORENA ZONE; U-PB; BOHEMIAN MASSIF; BOLU MASSIF; CONTINENTAL-MARGIN; Geology